The effect of second victim-related distress and support on work-related outcomes in tertiary care Hospitals in Kelantan, Malaysia: a cross sectional study using Malay revised second victim experience and support tool - Kamaruzaman, Ahmad Zulfahmi Mohd (2022)
Background: “Second victims” are defined as healthcare providers whom traumatized either by physical, psychological, reducing professional capability, or emotional as a result encountering any patient safety incidents. Organizational support (colleague, supervisor, and institutional support) is a crucial part to mitigate the second victims. If awfully treated, the second victims may subsequently progress to negative work-related outcomes, and in contrast, it cultivated resilience if their well-being is not compromised. As a method to assess the second victim syndrome in healthcare facility, The Revised Second Victim Experience and Support Tool (SVEST-R) was used. It was a well-established instrument and acknowledged worldwide. Hence, the aim of this study was firstly to evaluate the psychometric properties of the Malay version of SVEST-R. Then the next aim was to determine the factors affecting negative work-related outcomes and resilience with a hypothetical triad of support as the mediators: colleague, supervisor, and institutional support. Methods: The first part study was a cross sectional study recruiting a total of 350 healthcare professionals from a teaching hospital in Kelantan, Malaysia. After obtaining the permission from the original author, the instrument had undergone ten steps of established translation process guideline. Pre-testing of 30 respondents were done before embarked with the confirmatory factor analysis (CFA); evaluating internal consistency and construct validity. Then, the study continued with recruitment of 733 healthcare providers from another three tertiary care hospitals in Kelantan, Malaysia. Three steps of hierarchical linear regression were developed for both outcomes (negative work-related outcomes and resilience). Four multiple mediator models of the support triad were analysed using R software environment. Results: The final model for M-SVEST-R agreed for 7 factors and 32 items as the CFA suggested for good model fit. The internal consistency of using Raykov’s rho showed good result; ranged from 0.77 to 0.93 with the total rho of 0.83. In the regression model, second victim distress, professional efficacy, and the support triad contributed significantly in the regression models. Colleague support partially mediated the relationship defining the effects of professional efficacy on negative work-related outcomes and resilience, whereas colleague, supervisor support, and institutional support all partially mediated the effects of second victim distress on negative work-related outcomes. Similar results were found regarding resilience, with all support triads producing similar results. Conclusion: The M-SVEST-R demonstrated excellent psychometric properties with adequate validity and reliability, and readily used for any study concerning second victim. As mediators, the organizational support ameliorated the effect of second victim-related distress on resilience, suggesting an important role of having good support. However, instead of mitigating the negative work-related outcomes, some support scenarios increased the negative work-related outcomes due to possible concern of punitive culture of healthcare.